Symmetry of index process as means of artistic speech updating - Желязкова, Вікторія Валеріївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article is devoted to a symmetry problem of index signs and their ability to updating of syntactic links in the novel "Red Fish" by I. Hrigurko. The short review of works of scientists who were engaged in development of the theory of asymmetry / symmetry in language sign is submitted. Definitions of the concepts "index" and "symmetry" are named. Symmetry types the index with the indication of their part-speech representation are illustrated. The syntactic role symmetric the index signs recorded in the novel "Red Fish" is defined.